Women philosophers on autonomy
1 online resource (240 pages)
Keywords: We encounter autonomy in virtually every area of philosophy: in its relation with rationality, personality, self-identity, authenticity, freedom, moral values and motivations, and forms of government, legal, and social institutions. At the same time, the notion of autonomy has been the subject of significant criticism. Some argue that autonomy outweighs or even endangers interpersonal or collective values, while others believe it alienates subjects who don’t possess a strong form of autonomy. These marginalized subjects and communities include persons with physical or psychological disabilities, those in dire economic conditions, LGBTI persons, ethnic and religious minorities, and women in traditional communities or households.